Good Practice in Child Protection - Hobart, Christine; Frankel, Jill. (Cheltenham : Nelson Thornes, 2005)
'Good Practice in Child Protection' offers comprehensive guidance for all early years workers and students. The text includes coverage of legal issues, examines the roles of various child protection agencies, and gives advice on how to work with parents.
Previous ed.: Cheltenham: Stanley Thornes, 1998.
Includes bibliographical references and index.
Keywords: Child welfare; Society